Proceedings of the 60th Annual Meeting of the Association for Computational Linguistics (Volume 1: Long Papers) 2022
DOI: 10.18653/v1/2022.acl-long.142
|View full text |Cite
|
Sign up to set email alerts
|

Towards Robustness of Text-to-SQL Models Against Natural and Realistic Adversarial Table Perturbation

Abstract: The robustness of Text-to-SQL parsers against adversarial perturbations plays a crucial role in delivering highly reliable applications. Previous studies along this line primarily focused on perturbations in the natural language question side, neglecting the variability of tables. Motivated by this, we propose the Adversarial Table Perturbation (ATP) as a new attacking paradigm to measure the robustness of Textto-SQL models. Following this proposition, we curate ADVETA, the first robustness evaluation benchmar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…In contrast, with LLM-based parsers, researchers focuse on eliciting reasoning and self-correction capabilities in LLMs by designing better prompts. However, although some work has explored the adversarial robustness of NLIDB (Gan et al, 2021;Pi et al, 2022), few studies have pointed out the potential security risks emerging from malicious user interaction.…”
Section: Related Workmentioning
confidence: 99%
“…In contrast, with LLM-based parsers, researchers focuse on eliciting reasoning and self-correction capabilities in LLMs by designing better prompts. However, although some work has explored the adversarial robustness of NLIDB (Gan et al, 2021;Pi et al, 2022), few studies have pointed out the potential security risks emerging from malicious user interaction.…”
Section: Related Workmentioning
confidence: 99%
“…Nevertheless, our approach performs strongly for error detection as it can still effectively capture semantic errors that are free from schema linking mistakes. This can be explained by the high column mention rate in Spider (Pi et al, 2022). Future work could develop more effective entity linking mechanisms to extend our model to more challenging testing environments where schema linking errors are more common.…”
Section: Limitationsmentioning
confidence: 99%
“…Recently, the reliability of Text-to-SQL algorithms, and code generation systems more generally, has attracted increasing attention. A number of researchers (e.g., Zeng et al [28], Deng et al [29], and Pi et al [30]) reported that perturbing the input questions or table columns may impact the performance of Text-to-SQL algorithms significantly, but none of them has explored whether the model input could threaten the connected database. Nguyen and Nadi [31] and Vasconcelos et al [32] noticed that code generated by GitHub Copilot (which is based on Codex) often contains errors, where Perce et al [33] further observed web security vulnerabilities.…”
Section: (Un)reliability Of Code Generationmentioning
confidence: 99%